Mild Thyrotoxicosis Leads to Brain Perfusion Changes: An Arterial Spin Labelling Study. (9th January 2017) - Göbel, A.; Heldmann, M.; Sartorius, A.; Göttlich, M.; Dirk, A.‐L.; Brabant, G.; Münte, T. F.
Abstract : Hypo‐ and hyperthyroidism have effects on brain structure and function, as well as cognitive processes, including memory. However, little is known about the influence of thyroid hormones on brain perfusion and the relationship of such perfusion changes with cognition. The present study aimed to demonstrate the effect of short‐term experimental hyperthyroidism on brain perfusion in healthy volunteers and to assess whether perfusion changes, if present, are related to cognitive performance. It is known that an interaction exists between brain perfusion and cerebral oxygen consumption rate and it is considered that neural activation increases cerebral regional perfusion rate in brain areas associated with memory. Measuring cerebral blood flow may therefore represent a proxy for neural activity. Therefore, arterial spin labelling (ASL) measurements were conducted and later analysed to evaluate brain perfusion in 29 healthy men before and after ingesting thyroid hormones for 8 weeks. Psychological tests concerning memory were performed at the same time‐points and the results were correlated with the imaging results. In the hyperthyroid condition, perfusion was increased in the posterior cerebellum in regions connected with cerebral networks associated with cognitive control and the visual cortex compared to the euthyroid condition. In addition, these perfusion changes were positively correlated with changes of performance in the German version of the Auditory Verbal Learning Task [AVLT, Verbaler Lern‐und‐Merkfähigkeits‐Test (VLMT)]. Cerebellar perfusion and function therefore appears to be modulated by thyroid hormones, likely because the cerebellum hosts a high number of thyroid hormone receptors.